Avoiding Forward Car Collision using Stereo Vision System - Surgailis, Tadas; Valinevicius, Algimantas; Markevicius, Vytautas; Navikas, Dangirutis; Andriukaitis, Darius (Elektronika ir Elektrotechnika, 2012)
This paper presents a model of stereo vision system for intelligent vehicles to avoid forward car collision. Approached vehicle extraction and distance estimation algorithm based on dense edge map calculation and ROI filter. Primary experiments have been executed modeling vision system in a virtual computer reality. Special developed software has been used to simulate virtual environment and vision system. Results shows that approached algorithm successfully extracted not only vehicles but and other potential obstacles, such as, pedestrians. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2609